Relevance of superoxide dismutase type 1 to lipoid pneumonia: the first retrospective case-control study - Yinan Hu; Yanhong Ren; Yinzhen Han; Zhen Li; Weiqing Meng; Yuhui Qiang; Mengyuan Liu; Huaping Dai (Respiratory Research)
Abstract Background Lipoid pneumonia (LP) is a rare disease caused by the accumulation of lipids and lipid-laden macrophages in the alveoli inducing damage. LP is difficult to differentiate from other similar diseases without pathological evidence, such as upper respiratory tract infection (URTI), pneumonia, cryptogenic organizing pneumonia (COP), pulmonary alveolar proteinosis (PAP), lung mucinous adenocarcinoma and pulmonary edema. Given the high misdiagnosis rate and limited statistical clinical and treatment data, there is an urgent need for novel indicators of LP. Superoxide dismutase type1 (SOD1) plays an essential role in macrophage polarization, promoting inflammation and oxidative stress, but its association with LP remains unknown. Methods The clinical data of 22 patients with proven LP from January 2008 to June 2024 and their prognostic information up to June 2024 were retrospectively gathered (ClinicalTrials.gov, NCT06430008). Additionally, information on patients with URTI, bacterial and fungal pneumonia, COP, PAP, lung mucinous adenocarcinoma and pulmonary edema, was collected totaling 140 patients as control subjects. Receiver operating characteristic curve, machine learning (ML), regression and survival analyses were performed to analyze the data. Results In multivariate regression analysis, the sole independent risk factor of LP was the level of SOD1 (OR 0.922, 95% CI: 0.878 ~ 0.967, P < 0.001), while smoking status (β= -0.177, 95% CI -18.645~-2.836, P = 0.008), diabetes mellitus (β= -0.191, 95% CI: -20.442~-3.592, P = 0.005), and total sialic acid (TSA) (β= -0.426, 95% CI: -0.915~ -0.433, P < 0.001) independently influenced the level of SOD1. SOD1 had the highest importance score in ML-based LP predictive models. Additionally, advanced age may be associated with higher mortality in LP. Conclusion SOD1 is a potential biomarker for LP, but the smoking status, diabetes comorbidities, and TSA level need to be considered.